2021
DOI: 10.48550/arxiv.2110.00643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distributed $Δ$-Coloring Plays Hide-and-Seek

Abstract: We prove several new tight or near-tight distributed lower bounds for classic symmetry breaking graph problems. As a basic tool, we first provide a new insightful proof that any deterministic distributed algorithm that computes a ∆-coloring on ∆-regular trees requires Ω(log ∆ n) rounds and any randomized algorithm requires Ω(log ∆ log n) rounds. We prove this result by showing that a natural relaxation of the ∆-coloring problem is a fixed point in the round elimination framework.As a first application, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For the proof of Theorem 3.4, we will make use of an approach that is an extension of the approach known for the setting of LCLs on regular trees without inputs (see, e.g., [5,7,6]). More specifically , we will explicitly define an algorithm A 1 (depending on A) that satisfies the properties stated in Theorem 3.4.…”
Section: From Harder To Easier Problemsmentioning
confidence: 99%
“…For the proof of Theorem 3.4, we will make use of an approach that is an extension of the approach known for the setting of LCLs on regular trees without inputs (see, e.g., [5,7,6]). More specifically , we will explicitly define an algorithm A 1 (depending on A) that satisfies the properties stated in Theorem 3.4.…”
Section: From Harder To Easier Problemsmentioning
confidence: 99%
“…As a result, we therefore also obtain O(∆ + log * n)-round algorithms for MIS and maximal matching. In [3,4,15], it was shown that for MIS and maximal matching, this bound is tight, even on tree networks. More specifically, it was shown that there is no randomized MIS or maximal matching algorithm with round complexity o ∆ + log log n log log log n and there is no deterministic such algorithm with round complexity o ∆ + log n log log n .…”
Section: Introductionmentioning
confidence: 99%